Nonvirally modified autologous primary hepatocytes correct diabetes and prevent target organ injury in a large preclinical model. - Nelson K F Chen (Public Library of Science (PLoS), 2008)
Background Current gene- and cell-based therapies have significant limitations which impede widespread clinical application. Taking diabetes mellitus as a paradigm, we have sought to overcome these limitations by ex vivo electrotransfer of a nonviral insulin expression vector into primary hepatocytes followed by immediate autologous reimplantation in a preclinical model of diabetes. Methods and results In a single 3-hour procedure, hepatocytes were isolated from a surgically resected liver wedge, electroporated with an insulin expression plasmid ex vivo and reimplanted intraparenchymally under ultrasonic guidance into the liver in each of 10 streptozotocin-induced diabetic Yorkshire pigs. The vector was comprised of a bifunctional, glucose-responsive promoter linked to human insulin cDNA. Ambient glucose concentrations appropriately altered human insulin mRNA expression and C-peptide secretion within minutes in vitro and in vivo. Treated swine showed correction of hyperglycemia, glucose intolerance, dyslipidemia and other metabolic abnormalities for > or = 47 weeks. Metabolic correction correlated significantly with the number of hepatocytes implanted. Importantly, we observed no hypoglycemia even under fasting conditions. Direct intrahepatic implantation of hepatocytes did not alter biochemical indices of liver function or induce abnormal hepatic lobular architecture. About 70% of implanted hepatocytes functionally engrafted, appeared histologically normal, retained vector DNA and expressed human insulin for > or = 47 weeks. Based on structural tissue analyses and transcriptome data, we showed that early correction of diabetes attenuated and even prevented pathological changes in the eye, kidney, liver and aorta. Conclusions We demonstrate that autologous hepatocytes can be efficiently, simply and safely modified by electroporation of a nonviral vector to express, process and secrete insulin durably. This strategy, which achieved significant and sustained therapeutic efficacy in a large preclinical model without adverse effects, warrants consideration for clinical development especially as it could have broader future applications for the treatment of other acquired and inherited diseases for which systemic reconstitution of a specific protein deficiency is critical.